2017
DOI: 10.4136/ambi-agua.1992
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência e remoção de estrogênios por processos de tratamento biológico de esgotos

Abstract: Os estrogênios são micropoluentes capazes de causar alterações no sistema endócrino de organismos aquáticos. Uma das principais fontes da sua introdução no meio hídrico é através do lançamento de esgotos domésticos. Este artigo apresenta uma revisão sobre a ocorrência dos estrogênios estrona, estradiol, estriol e etinilestradiol em esgotos brutos e tratados e em águas superficiais, bem como sobre sua remoção por diferentes processos de tratamento biológico de esgoto. Os poucos trabalhos realizados no Brasil mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
(49 reference statements)
0
5
0
4
Order By: Relevance
“…For example, Auriol et al (2006) reported a range between 3 and 7.1 ng L -1 of EE2 in raw sewage from some European countries, and Luo et al (2014) reported EE2 concentrations in raw sewage between 1 and 3 ng L -1 in different European countries, Asia and the United States. Cunha et al (2017) reported a range between 12.4 and 3,180 ng L -1 for EE2 in raw sewage in different areas in Brazil. These variations in EE2 concentrations in raw sewage may occur due to differences in birth control and public health policies (Jafari et al, 2009).…”
Section: Ee2 Residues In Sewage Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Auriol et al (2006) reported a range between 3 and 7.1 ng L -1 of EE2 in raw sewage from some European countries, and Luo et al (2014) reported EE2 concentrations in raw sewage between 1 and 3 ng L -1 in different European countries, Asia and the United States. Cunha et al (2017) reported a range between 12.4 and 3,180 ng L -1 for EE2 in raw sewage in different areas in Brazil. These variations in EE2 concentrations in raw sewage may occur due to differences in birth control and public health policies (Jafari et al, 2009).…”
Section: Ee2 Residues In Sewage Samplesmentioning
confidence: 99%
“…Finally, a small amount of EE2 present in treated sewage (about 1.0 ng L -1 ) may be released daily into Paranoá Lake. This concentration represents a risk to the aquatic environment since it can cause vitellogenin induction in male fish (Cunha et al, 2017). Therefore, further studies in real scale sewage treatment plants applying different methods (processes) are required to better elucidate this phenomenon, mainly under higher phosphorus removal rates.…”
Section: Ee2 Residues In Sewage Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…O monitoramento de fármacos residuais no meio ambiente indica a frequente presença dessas substâncias em efluentes de ETE e águas superficiais em concentrações na faixa de µg.L -1 e ng.L -1 (STELATO et al, 2016;CUNHA et al, 2017;SHARMA et al, 2019). Mesmo em concentrações baixas (ng.L -1 ), essas substâncias podem causar efeitos adversos aos seres vivos.…”
Section: Introductionunclassified
“…Neste caso, a gestão de medicamentos e de seus resíduos no Brasil poderia se basear nas mesmas estratégias adotadas para os agrotóxicos. Para que este mecanismo possa ser usado seria necessária à obtenção de dados sobre a ocorrência desses resíduos na água superficial e na usada para consumo humano, o que ainda é pouco discutido e pesquisado no Brasil 57 . Esta medida deveria incluir as companhias de saneamento responsáveis pelos serviços de água e esgoto para alimentar os dados de risco ambiental.…”
unclassified